The Honey bee across the curriculum - Sue Hart (Environmental Association of Southern Africa, 1987)
This paper describes a teacher aid programme on the honeybee, which is considered an ideal subject for cross-curricula study. The rationale of development is outlined and the content of the tape, wall charts and handbook are discussed. Examples from the teacher's handbook are given.